Answer:
The quadratic equation for the given roots 6 , [tex]\frac{2}{3}[/tex] is y = 3 x² - 20 x + 12
Step-by-step explanation:
Given as :
The roots of the quadratic equation are 6 , [tex]\frac{2}{3}[/tex]
Let The standard quadratic equation
a x² + b x + c = 0
So, the roots are [tex]\alpha[/tex] = 6
And [tex]\beta[/tex] = [tex]\frac{2}{3}[/tex]
Sum of roots = [tex]\alpha +\beta[/tex]
i.e [tex]\alpha +\beta[/tex] = 6 + [tex]\frac{2}{3}[/tex] = [tex]\frac{20}{3}[/tex]
The quadratic equation
y = (x - α) (x - β)
Or, y = (x - 6) (x - [tex]\frac{2}{3}[/tex])
Or, y = x² - [tex]\frac{2}{3}[/tex] x - 6 x + (6 × [tex]\frac{2}{3}[/tex])
Or, y = x² - ( [tex]\frac{2}{3}[/tex] + 6) x + 4
Or, y = x² - ([tex]\frac{2+18}{3}[/tex] ) x + 4
Or, y = x² - [tex]\frac{20}{3}[/tex]x + 4
Or, y = 3 x² - 20 x + 12
Hence, The quadratic equation for the given roots 6 , [tex]\frac{2}{3}[/tex] is y = 3 x² - 20 x + 12 . Answer